2018
DOI: 10.1007/s11600-018-0194-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the primary and secondary microseisms in the wavefield of the ambient noise recorded in northern Poland

Abstract: Seasonal changes of the primary and secondary microseisms were analysed in the wavefield of the ambient noise recorded during the entire 2014 at the ''13 BB star'' array located in northern Poland, composed of thirteen, symmetrically arranged, broadband seismic stations. To that, spectral analysis, seismic interferometry, surface scalar wind speed distribution, and beamforming were used. Spectral analysis allowed to observe that a splitting of the secondary microseism peak was present in winter and autumn, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…Hence, the classical location algorithms, used in earthquake seismology and based on the picking of the different seismic phases, cannot be applied to locate microseism sources. Array processing techniques can overcome the above-mentioned difficulties and provide information on the microseism source areas that generally coincide with coastal regions and/or oceanic storm systems (e.g., Chevrot et al, 2007;Juretzek and Hadziioannou, 2017;Pratt et al, 2017;Lepore and Grad, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the classical location algorithms, used in earthquake seismology and based on the picking of the different seismic phases, cannot be applied to locate microseism sources. Array processing techniques can overcome the above-mentioned difficulties and provide information on the microseism source areas that generally coincide with coastal regions and/or oceanic storm systems (e.g., Chevrot et al, 2007;Juretzek and Hadziioannou, 2017;Pratt et al, 2017;Lepore and Grad, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that secondary microseisms are dominated by Rayleigh waves (Lee 1935;Lacoss et al 1969;Tanimoto et al 2006); however, recent studies have shown that Love waves (Nishida et al 2008;Juretzek and Hadziioannou 2016;Gal et al 2017) can be detected in the secondary microseism frequency band. As reported in the literature (Bromirski et al 2005;Koper and Burlacu 2015;Lepore and Grad 2018;Xiao et al 2018), the secondary microseism sometimes splits into two peaks, involving the simultaneous activation of two oceanic source regions. The first peak corresponds to the long-period double-frequency (LPDF) microseism (0.1-0.25 Hz), while the second one, to the short-period double-frequency (SPDF) microseism (0.25-0.8 Hz).…”
Section: Introductionmentioning
confidence: 61%
“…The description of spatial and temporal variations of the ambient noise wavefield is fundamental for many aspects of seismology. Ambient noise can be used not only to infer the characteristics of ocean storms (Ebeling 2012), but also to evaluate the performance of seismic arrays (Wilson et al 2002) and to investigate the Earth's structure (Shapiro and Campillo 2004;Sabra et al 2005;Lepore and Grad, 2018). Temporal changes of the noise wavefield during strong ocean storms are consistent with the variations in the wave height and wavewave interaction (Friedrich et al 1998;Nishida et al 2008;Ardhuin et al 2011Ardhuin et al , 2015Obrebski et al 2012;Davy et al 2015;Möllhoff and Bean 2016).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…We observe that the secondary microseism noise level is minimum during local summer, with higher levels occurring during local winter when the Southern Ocean experiences violent winter storms. The relatively higher secondary microseisms in austral winter could also be explained by instances of icebreakups and near-coastal interactions related to iceberg reflections (Grob et al 2011;Davy et al 2016;Pratt et al 2017;Lepore & Grad 2018). For the primary microseism band, noise levels are reduced in the austral winter.…”
Section: Seasonal Variations Of Microseismic Signalmentioning
confidence: 99%